Pengaruh Media Pembelajaran Berbasis Artificial Intelligence (AI) Menggunakan Quizizz terhadap Motivasi Belajar Siswa Kelas VII di SMP Negeri 2 Sungai Pua Kabupaten Agam - Nita Fitriani; Zulfani Sesmiarni (MASALIQ, 2026)
The low learning motivation of seventh-grade students at SMP Negeri 2 Sungai Pua, Agam Regency, is associated with instruction that remains dominated by conventional methods, resulting in students being less active and less interested in participating in the learning process. This study aimed to analyze the effect of using artificial intelligence (AI)-based learning media through Quizizz on students’ learning motivation. The study employed a quantitative approach with a quasi-experimental method and a nonequivalent control group design. The study population comprised all 42 seventh-grade students in the 2025/2026 academic year. The sample was selected through purposive sampling, with class VII-1 serving as the experimental group and class VII-2 as the control group, each consisting of 21 students. Data were collected using a Likert-scale learning motivation questionnaire comprising 20 statement items based on Hamzah B. Uno’s six indicators of learning motivation. The data were analyzed using normality tests, homogeneity tests, an independent-samples t-test, a paired-samples t-test, and N-gain analysis. The results showed that the mean learning motivation score in the experimental group increased from 42.76 to 85.33, whereas that in the control group increased from 44.62 to 72.90. The independent-samples t-test showed a significant difference between the two groups (p < 0.05), whereas the paired-samples t-test in the experimental group showed a significant increase (p < 0.001). The N-gain score of the experimental group reached 0.7451, categorized as high, which was greater than the control group’s score of 0.5071, categorized as moderate. Thus, the use of AI-based learning media through Quizizz had a significant effect on increasing students’ learning motivation. These findings reinforce the importance of using technology-based learning media as an alternative for increasing students’ active participation and motivation in the learning process.